Dari Kepuasan Hingga Kesetiaan: Menelusuri Faktor Penentu Kesetiaan Pelanggan dalam Layanan E-Grocery - Orlando, James; Keni, Keni (MBIA, 2025)
The development of e-grocery increased dramatically after the COVID-19 pandemic. The application's ease of use is the main reason customers use it. However, the development occurred along with an increasing number of e-grocery applications, which tightened competition that can be a barrier to improving customer loyalty. Therefore, this study examined whether customer attachment, perceived value, and customer experience can positively predict customer satisfaction and loyalty, and the mediating role of customer satisfaction. This study uses a non-probability sampling method with a convenience sampling technique. The sample was selected using a Google Form distributed online through social media. One hundred sixty-eight respondents were collected and analyzed in this study using partial least squares structural equation modelling (PLS-SEM). This study concluded that customer attachment, perceived value, and experience can positively and significantly predict customer satisfaction and loyalty. Moreover, customer satisfaction predicts customer loyalty positively and significantly. Finally, customer satisfaction can positively and significantly mediate the prediction of emotional attachment, perceived value, and customer experience on customer loyalty. This study suggests that an e-grocery application can improve its service to increase customer loyalty. The improvement can be conducted by providing a responsive customer service and offering a wide variety of products, so that customers can feel that they can purchase many daily needs through the application. Keywords: emotional attachment, perceived value, customer experience, customer satisfaction, customer loyalty Abstrak Perkembangan e-grocery meningkat secara drastis setelah adanya pandemi Covid-19. Kemudahan dalam penggunaan aplikasi e-grocery menjadi alasan utama pelanggan untuk terus menggunakan aplikasi tersebut. Peningkatan jumlah aplikasi e-grocery kemudian meningkatkan persaingan, sehingga kesetiaan pelanggan menjadi sulit untuk terbentuk. Penelitian ini dilakukan untuk menguji apakah keterikatan pelanggan, nilai yang dirasakan, dan pengalaman pelanggan dapat memprediksi secara positif terhadap kepuasan pelanggan dan kesetiaan pelanggan, serta peran mediasi kepuasan pelanggan. Penelitian ini menggunakan metode non-probability sampling dengan teknik convenience samplimg sebagai metode untuk pemilihan sampel melalui Google Form yang didistribusikan secara online melalui media sosial. Penelitian ini memperoleh data dari 168 responden yang dianalisis dengan menggunakan metode Partial Least Square – Structural Equation Model (PLS-SEM). Hasil menunjukkan bahwa keterikatan pelanggan, nilai yang dirasakan, dan pengalaman pelanggan dapat memprediksi secara positif dan signifikan terhadap kepuasan pelanggan dan kesetiaan pelanggan. Kemudian, kepuasan pelanggan memprediksi secara positif dan signifikan kesetiaan pelanggan. Kepuasan pelanggan juga ditemui dapat memediasi secara positif dan signifikan pada keterikatan emosional, nilai yang dirasakan, dan pengalaman pelanggan terhadap kesetiaan pelanggan. Penelitian ini mengimplikasikan bahwa aplikasi e-grocery dapat mengembangkan layanannya untuk meningkatkan loyalitas pelanggan melalui customer service yang responsif dan menyediakan pilihan produk yang beragam.   Kata kunci: keterikatan emosional, nilai yang dirasakan, pengalaman pelanggan, kepuasan pelanggan, kesetiaan pelanggan